Determination of the optical properties of Intralipid 20% over a broadband spectrum - Shahin, Ali; Sayem El-Daher, Moustafa; Bachir, Wesam (Photonics Letters of Poland, 2018)
The aim of this study is to characterize the optical properties of Intralipid20% using two methods modified Kubelka-Munk model and Mie theory and to test the applicability of a modified Kubelka-Munk model with a single integrating sphere system over a wide wavelength range 470 – 725nm. Scattering coefficients which estimated by these two methods were matched and the absorption effect was observed and quantified. Finally, the imaginary part of the refractive index was estimated besides scattering, absorption and anisotropy coefficients. Full Text: PDF References B.W. Pogue, and M.S. Patterson, "Review of tissue simulating phantoms for optical spectroscopy, imaging and dosimetry", J. Biomed. Opt. 11, 4(2006). CrossRef J. Hwang, C. Ramella-Roman, and R. Nordstrom, "Introduction: Feature Issue on Phantoms for the Performance Evaluation and Validation of Optical Medical Imaging Devices", Biomed. Opt. Express. 3, 6(2012). CrossRef P. Ninni, F. Martelli, and G. Zaccanti, "Intralipid: towards a diffusive reference standard for optical tissue phantoms", Phys. Med. Biol 56, 2(2011). CrossRef S. Flock, S. Jacques, B. Wilson, W. Star, and J.C. van Gemert, "Optical properties of intralipid: A phantom medium for light propagation studies", Lasers. Surg. Med 4, 12(1992). CrossRef R. Michels, F. Foschum, and A. Kienle, "Optical properties of fat emulsions", Opt. Express. 16, 8(2008). CrossRef L. Spinelli et al. "Calibration of scattering and absorption properties of a liquid diffusive medium at NIR wavelengths. Time-resolved method", Opt. Express. 15, 11(2007). CrossRef L. Spinelli et al. "Determination of reference values for optical properties of liquid phantoms based on Intralipid and India ink", Biomed. Opt. Express. 5, 7(2014). CrossRef H. van Staveren, C. Moes, J. van Marle, S. Prahl, and J. van Gemert, "Light scattering in lntralipid-10% in the wavelength range of 400–1100 nm", Appl. Opt. 30, 31(1991). CrossRef B. Wilson, M. Patterson, and S. Flock, "Indirect versus direct techniques for the measurement of the optical properties of tissues", Photochem. Photobiol. 46, 5(1987). CrossRef H. Soleimanzad, H. Gurden, and F. Pain, "Optical properties of mice skull bone in the 455- to 705-nm range", J. Biomed. Opt. 22, 1(2017). CrossRef C. Holmer et al. "Optical properties of adenocarcinoma and squamous cell carcinoma of the gastroesophageal junction", J. Biomed. Opt. 12, 1(2007). CrossRef S. Thennadil, "Relationship between the Kubelka–Munk scattering and radiative transfer coefficients", OSA. 25, 7(2008). CrossRef L. Yang, and B. Kruse, "Qualifying the arguments used in the derivation of the revised Kubelka–Munk theory: reply", OSA. 21, 10(2004). CrossRef W. Vargas, and G. Niklasson, "Applicability conditions of the Kubelka–Munk theory", Appl. Opt. 36, 22(1997). CrossRef A. Krainov, A. Mokeeva, E. Segeeva, P. Agrba, and M. Kirillin, "Optical properties of mouse biotissues and their optical phantoms", Opt. Spec. 115, 2(2013). CrossRef H.C. van de Hulst, Light Scattering by Small Particles. (New York, Dover Publication 1981). CrossRef C. Matzler, Matlab Functions for Mie Scattering and Absorption. (Bern, Bern university 2002). DirectLink C. Matzler, Matlab Functions for Mie Scattering and Absorption, version 2 (Bern, Bern university 2002). DirectLink G. Segelstein, The complex refractive index of water [dissertation]. (Kansas, university of Missouri-Kansas city 1981). DirectLink A. Shahin, and W. Bachir, Pol. J. Med. Phys. Eng. 21, 4(2017). CrossRef